FPGA Synthesis of Reconfigurable Modules for FIR Filter - Saranya R; Pradeep C; Neena Baby; Radhakrishnan R (International Journal of Reconfigurable and Embedded Systems (IJRES), 2015)
Reconfigurable computing for DSP remains an active area to explore as the need for incorporation with more conventional DSP technologies turn out to be obvious. Conventionally, the majority of the work in the area of reconfigurable computing is aimed on fine grained FPGA devices. Over the years, the focus is shifted from bit level granularity to a coarse grained composition. FIR filter remains and persist to be an important building block in various DSP systems. It computes the output by multiplying input samples with a set of coefficients followed by addition. Here multipliers and adders are modeled using the concept of divide and conquer. For developing a reconfiguarble FIR filter, different tap filters are designed as separate reconfigurable modules. Furthermore, there is an additional concern for making the system fault tolerant. A fault detection mechanism is introduced to detect the faults based on the nature of operands. The reconfigurable modules are structurally modeled in Verilog HDL and simulated and synthesized using Xilinx ISE 14.2. A comparison of the device utilization of reconfigurable modules is also presented in this paper by implementing the design on various Virtex FPGA devices.